Humeral Stem Designs in Reverse Total Shoulder Arthroplasty: A Focus on the Adjustability of Inclination, Torsion, and Version - Abdelkader Shekhbihi; Philipp Moroder (The Hive)
Background: While the inclination of the humeral component in reverse total shoulder arthroplasty (rTSA) has been extensively studied, less attention has been given to the parameters of version and torsion. These parameters, which influence outcomes in rTSA, warrant closer examination. This study aims to analyze the designs of humeral stems in rTSA, focusing on their ability to independently adjust inclination (coronal plane), torsion (axial plane), and version (sagittal plane). We hypothesize that while most designs allow for inclination and torsion adjustments, independent version adjustment is rare and may offer unique biomechanical implications.